1999
DOI: 10.1038/sj.bjc.6690456
|View full text |Cite
|
Sign up to set email alerts
|

Amphiregulin acts as an autocrine growth factor in two human polarizing colon cancer lines that exhibit domain selective EGF receptor mitogenesis

Abstract: Summary Colonic enterocytes, like many epithelial cells in vivo, are polarized with functionally distinct apical and basolateral membrane domains. The aims of this study were to characterize the endogenous epidermal growth factor (EGF)-like ligands expressed in two polarizing colon cancer cell lines, HCA-7 Colony 29 (HCA-7) and Caco-2, and to examine the effects of cell polarity on EGF receptor-mediated mitogenesis. HCA-7 and Caco-2 cells were grown on plastic, or as a polarized monolayer on Transwell filters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 37 publications
3
60
0
1
Order By: Relevance
“…Moreover, we could measure the increase of TGF-␣ concentration in the culture medium of PAR2 agonist-stimulated HT-29 cells. Amphiregulin, another EGF-R ligand, has been shown to also be expressed in colon cancer (28,29). Involvement of amphiregulin in PAR2-mediated EGF-R transactivation in HT-29 cells is unlikely for the following reasons: (i) incubation of HT-29 cells with neutralizing antibody against TGF-␣ in the culture medium completely blocks PAR2-induced cell proliferation; and (ii) neutralizing antibodies against bioactive amphiregulin did not alter the HT-29 cell proliferation induced by PAR2 agonists.…”
Section: Par2 Transactivates Egf-r In Colon Cancermentioning
confidence: 99%
“…Moreover, we could measure the increase of TGF-␣ concentration in the culture medium of PAR2 agonist-stimulated HT-29 cells. Amphiregulin, another EGF-R ligand, has been shown to also be expressed in colon cancer (28,29). Involvement of amphiregulin in PAR2-mediated EGF-R transactivation in HT-29 cells is unlikely for the following reasons: (i) incubation of HT-29 cells with neutralizing antibody against TGF-␣ in the culture medium completely blocks PAR2-induced cell proliferation; and (ii) neutralizing antibodies against bioactive amphiregulin did not alter the HT-29 cell proliferation induced by PAR2 agonists.…”
Section: Par2 Transactivates Egf-r In Colon Cancermentioning
confidence: 99%
“…AR, an EGF-related growth factor produced by epithelial cells, functions as an autocrine/paracrine cell proliferation factor (42,43). Several lines of evidence suggest that AR is an autocrine growth factor in human carcinoma cells (44 -51) and tumorigenicity of a human breast epithelial cell line is abolished by treatment with AR antisense (49).…”
Section: Ar and Igf1 Inhibit Serum Deprivation Apoptosis Of H358 And mentioning
confidence: 99%
“…4 In human malignancies overexpression or amplification of the EGFR has been shown to have an important role as activation of the EGFR initiates a cascade of phosphorylations that results in DNA synthesis and cell replication. [5][6][7][8] Therefore, presence or overexpression of the EGFR could give malignant cells a growth advantage. Furthermore, it has been shown that presence of the EGFR results in invasive tumors, higher stages of disease or disease progression.…”
mentioning
confidence: 99%